Do Environmental Prompts Work the Same for Everyone? A Test of Environmental Attitudes as a Moderator - Moussaoui, Lisa Selma; Desrichard, Olivier; Milfont, Taciano L. (Frontiers in Psychology, 2020)
The extant literature has focused either on personal variables or on situational factors to explain pro-environmental behavior, despite several calls to integrate both. The present research addresses this integration call by testing the interaction between environmental attitudes and situational prompts on pro-environmental behavior. Three experimental studies manipulate presence/absence of pro-environmental prompts, measure environmental attitudes, and investigate the effect of both variables on behavior. Study 1 showed a simple effect: participants with higher levels of pro-environmental attitudes (compared to those with lower levels) performed more the energy saving behavior in the presence of prompts. However, in the absence of prompt, none of the participants performed the behavior, which prevented us to statistically test the interaction. Study 2 and 3 were conducted with a similar design: main effects of attitude and prompts were obtained, but the interaction was not found. Bayesian analysis of the data suggests more evidence toward the null hypothesis of no interaction between environmental attitudes and situational prompts.